Heat treatment to modify the structural and physical properties of chitosan-based films - Rivero, Sandra G. M. (2012)
This work was focused on studying the changes undergone by heat-treated chitosan films with and without tannic acid addition by monitoring both microstructure and physical properties. Once the films were submitted to different heat treatments, they exhibited higher barrier properties as well as lower water uptake, solubility, and moisture content. These results were also confirmed through X-ray patterns, which changed from the hydrated to the anhydrous conformation, sharper FTIR peaks specifically associated with water, and shift of Tg toward higher temperatures determined by DMA. Moreover, the modifications caused by the curing process at a molecular scale were observed at a structural level by using a TEM technique. FTIR evaluation granted new insights into the interactions between tannic acid and chitosan molecules, before and after the heat curing, especially due to the occurrence of new peaks and changes in the wavenumber region 1550−1750 cm−1.